Spiral Jetty, thirty-seven years later: The cinematic time of James Benning. (1st October 2013) - Butler, Alison
This article considers cinematic time in James Benning's film, casting a glance (2007), in relation to its subject, Robert Smithson's 1970 earthwork Spiral Jetty, and his film of the same name. The radicalism of Smithson's thinking on time has been widely acknowledged, and his influence continues to pervade contemporary artistic practice. The relationship of Benning's films with this legacy may appear somewhat oblique, given their apparent phenomenological rendition of 'real time'. However, closer examination of Benning's formal strategies reveals a more complex temporal construction, characterized by uncertain intervals that interrupt the folding of cinematic time into the flow of consciousness. Smithson's film uses cinematic analogy to gesture towards vast reaches of geological time; Benning's film creates a simulated timescale to evoke the short history of the earthwork itself. Smithson's embrace of the entropic was a counter-cultural stance at the end of the1960s, but under the shadow of ecological disaster, this orientation has come to appear melancholy and romantic rather than radical. Benning's film returns the jetty to anthropic time, but raises questions about the ways we inhabit time. His practice of working with 'borrowed time' is particularly suited to the cultural and historical moment of his later work.